(3TQM ebOeI cTa GdZWGAs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3bO GdJeS HYV GdCUMGH Cf CTQM ebOeI cTa GdZWGA ddhGdO (B.. (3GdeTJedI Ydi GdeWGdH GdCUhdjI TQMG efGSHG dgG aCLHJge deG SCdhG JGQcG GdJWhjd eMGaXG Ydi LGOI GdGNJUGQ (B....s
(3BNQgG (B:s
.. (3hdh JYGQVJ COdI GdSff ef GdQhGjGJ GdVYjaI hGdTgQI hCbhGd GdYdeGA hLH GdJQLjM hEdG aGdWQM Ydi GdCXgQ (B.. (3dJfHjg GdZGadjf Yf GdCUhd GdcdjI hEdG addabjg aj GdeSGFd GdLRFjI (B.. (3hef edGMXI GdCNHGQ hcdGe GdYdeGA GdCHQGQ (B.s
(3aj BNQg ahGFO HNW eGdcg , jdjgG agQSJ JaUjdj ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\186s
(3eYLe GdeDdajf (B1\543s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs